Fuel suitability for homogeneous charge compression ignition combustion. (1st July 2016) - Yousefi, Amin; Birouk, Madjid
Highlights: Probability of partial combustion for natural gas case under low engine load. Methanol and NG/DME cases experience complete combustion under low engine load. At low engine load, NG/DME increases IMEP by 1.85% and 16.6% w.r.t NG and methanol. For ER > 0.26, IMEP decreases by 13% and 16% for methanol and NG/DME w.r.t NG. NG/DME and methanol have better performance and emissions at low to moderate loads. Abstract: The main focus of this paper is to investigate the impact of fuel type on HCCI combustion under different engine loads. A coupled chemical kinetics-computational fluid dynamic (CFD) model is developed to investigate the combustion performance and emissions characteristics of a HCCI engine with pre-combustion chamber fueled with natural gas, natural gas/10% dimethyl ether (DME) mixtures, or methanol. The simulation results indicate that the probability of partial combustion increases when using natural gas under low engine load. However, methanol and natural gas/DME experience complete combustion under low engine load. In contrast, for both methanol and natural gas/DME the rate of pressure rise and heat release at high engine load is very high which induces engine knock. At leaner mixtures (ER < 0.26), natural gas/DME attains the highest indicated mean effective pressure (IMEP) compared to that of methanol and natural gas. However, natural gas fueled HCCI engine has the highest IMEP under rich mixture conditions (ER > 0.26). NOx emissions of natural gas fueled HCCI engine are much lower than that of methanol and natural gas/DME, especially at high engine loads. However, natural gas/DME and methanol offer superior combustion control and NOx, carbon monoxide (CO), and unburned hydrocarbon (UHC) emissions under low to moderate engine loads. However, the use of natural gas in HCCI combustion is suitable for moderate to high engine loads.